A Bis(µ‐chlorido)‐Bridged Cobalt(II) Complex with Silyl‐Containing Schiff Base as a Catalyst Precursor in the Solvent‐Free Oxidation of Cyclohexane. Issue 37 (10th October 2017) - Zaltariov, Mirela‐Fernanda; Vieru, Veacheslav; Zalibera, Michal; Cazacu, Maria; Martins, Nuno M. R.; Martins, Luísa M. D. R. S.; Rapta, Peter; Novitchi, Ghenadie; Shova, Sergiu; Pombeiro, Armando J. L.; Arion, Vladimir B.
Abstract : A new bis(µ‐chlorido)‐bridged cobalt(II) complex [Co2 (µ‐Cl)2 (HL 2 )4 ][CoCl4 ] (1 ), where HL 2 is a silyl‐containing Schiff base, was synthesised. The structure of this compound was established by X‐ray crystallography revealing a zwitterionic form adopted by the organic ligand. The temperature dependence of the magnetic susceptibility and the field dependence of the magnetisation indicate the presence of ferromagnetic interactions between paramagnetic d 7 cobalt(II) centres ( S Co = 3/2). The exchange coupling parameter J (Co1–Co2) = +7.0 cm –1 extracted from broken‐symmetry (BS) DFT calculations agrees well with the value of +8.8 cm –1 determined from the experimental data by fitting them with the Hamiltonian H ^ = − J C o 1 − C o 2 e x c h S ^ C o 1 ⋅ S ^ C o 2 . Electrochemical studies indicate that complex1 is inefficient as a catalyst in electrochemical reduction of protons. One of the reasons is the low stability of the complex in solution. In contrast, 1 acts as an effective homogeneous (pre)catalyst in the microwave‐assisted neat oxidation of cyclohexane with aqueous t BuOOH (TBHP). The possible mechanism of catalytic oxidation and other advantages of using1 in the oxidation of cycloalkanes are discussed. Abstract : A new bis(µ‐chlorido)‐bridged cobalt(II) complex with a silyl‐containing tridentate Schiff base shows ferromagnetic behaviour at low temperatures, and acts as an effective homogeneous (pre)catalyst in the microwave‐assisted neat oxidation of cyclohexane with aqueous t BuOOH (TBHP) to cyclohexanol and cyclohexanone.